Disruptive innovation - Galetti, Michela; Špaček, Miroslav, 1954-; Demir, Ferhat; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The main objective of the master’s thesis is to address the evolution of contract lifecycle management, by means of incorporating disruptive innovation, specifically Generative AI. In the first part, the author provides a theoretical overview of concepts such as disruptive innovation and Generative AI, and how is the latter applied in the next generation of contract management. In the analytical part, the disruptive innovation will be applied to a German company operating in the IT sector, which has recently been involved in exploring the use of generative AI in the field of contract management. The primary data will be collected through surveys and interviews, which will be then analysed to provide an answer to the main problem. The advent of Generative AI, a branch of artificial intelligence, has undoubtedly brought considerable changes in today’s world, reshaping many areas of the businesses. Therefore, the company subject of the study uses Generative AI in the field of contract management, by making the contract creation more efficient and minimizing human error.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses